Use of non-prescription (OTC) analgesics - utilization pattern and user characteristics in Norway, The Tromsø study: Tromsø 6 - Salomonsson, Håkan Edvin Johannes (UiT Norges arktiske universitet, 2018)
Background: Drug policies in western countries, as well as countries in most other parts of the world, support self-medication with Over-The-Counter (OTC) drugs. The switch from prescription (Rx)-to-OTC has been most common in the Nordic countries, Great Britain and Germany in the last decades and deregulations were done to make it possible to sell OTC analgesics other places than under the pharmacy monopoly. The aim of the study is to describe where the different OTC analgesics are bought and how they are used in the population, and to assess whether or not recommended guidelines are followed. Material and method: A cross-sectional study was conducted based on data from the sixth survey of the Tromsø study, Tromsø 6, in 2007-2008. A specific questionnaire was given, on OTC analgesic use within the last four weeks before the interview, for the users of OTC analgesics. Conclusions: The majority of the adult OTC analgesic users in the present study follow the guidelines for use of OTC analgesics. Most of the OTC analgesics were used seldom and in a small daily dose. A small number of the participants report adverse effect from OTC analgesics. It is headache, muscle and joint pain and backache that is the main reasons for using OTC analgesics. The majority of the OTC analgesic users, use to buy there OTC analgesics at the pharmacy.